A importância da marca no consumo de tênis entre os adolescentes: suas relações com atitude e intenção de compra - Silinske, Jaqueline (2014)
The complexity in decision making by consumers is increasing, and human behavior is constantly changing, companies and consumers now live in a technological mediated both by society and by the media free access to the information in the interactions of purchase. This process becomes more difficult to understand when viewed in the context of life of young people who are forming their identity and personality. In this perspective, several studies attempt to identify the factors that explain the attitude and intention to buy, emerging the following question: What factors explain the attitude and intention to buy the fashion brand sneakers among students attending state public high school in Santa Maria/RS? To answer this question, this study aimed to examine the relationship of the constructs of Brand Consciousness, Materialism, Social Consciousness, fashion Innovativeness and Involvement with fashion about Attitude and Intention to buy tennis brand among high school students in state public school of Santa Maria/RS. A descriptive, causal and quantitative research was developed, using a survey adapted from the study realized by Zhang and Kim (2013) and applied to the high school students in the state system of Santa Maria/RS. Data collection was made with 1197 students of the high school spread over eight schools with the largest number of students in each administrative regions of Santa Maria/RS. The data analysis comprised univariate techniques, bivariate and multivariate analysis. In the initial model, the construct of Social Consciousness was removed from the analysis because the CS1 variable having a negative variance (-3.592) and CS2 present variable factor loading of 0.343. As a result, the final validated model based on the study of Zhang and Kim (2013) showed 6 constructs and 18 variables. It was noted that, Materialism (β=0.431) and brand consciousness (β=0.184) were positively related to Attitude Purchase fashion brand sneakers. The Attitude Purchase (β=0.562) was positively related to Purchase Intention of fashion brand sneakers. Based on the results of the Index Modification of AMOS software, regression weights indicated adjustments in the structural model proposed by Zhang and Kim (2013). Thus, there was the proposition of a model based on the study of Zhang and Kim (2013) for the context of students attending state public high school in Santa Maria/RS. In conclusion, the awareness of the brand (β=0.431), Materialism (β=0.398) and the fashion Involvement (β=0.222) were positively related to the intention to buy the brand sneakers.